Facial emotion recognition and its association with symptom severity, functionality, and cognitive impairment in schizophrenia: preliminary results - Johanna Vanessa Suárez-Salazar (Salud Mental, 2020)
Introduction There is evidence to suggest that individuals with schizophrenia have greater difficulty in recognizing facial emotions, which has been related to cognitive impairment and higher symptom severity in this disease and seems to lead to a worse functional prognosis.Objective To determine the association between facial emotion recognition and symptom severity, functionality, and cognitive impairment in a sample of schizophrenic patients.Method This is an observational, cross-sectional, and correlational study conducted on 72 patients. The following scales: PANSS, MOCA, ERI, and FACT-Sz were used to assess symptom severity in schizophrenia, cognitive functioning, facial emotion recognition, and functionality, respectively. The Pearson Correlation Coefficient was used to measure the linear association between all variables.Results Overall, moderate symptom severity and mild cognitive and functional disability were found. The most frequently recognized emotion was joy (70%) and the least frequently recognized one was anger. A positive association was also found between anger recognition and severity of the PANSS cognitive subscale (r = - .24, p = .03), sadness recognition and severity of the PANSS negative subscale (r = - .24, p = .03), and the FACT-Sz score and fear recognition (r = .31, p = .008).Discussion and conclusion The present study yields preliminary results that provide a broader perspective on facial emotion recognition and, indirectly, social interaction and functionality in people with schizophrenia.